The complete mitochondrial genome of Apis cerana-southern China (Hymenoptera: Apidae) and insights into the phylogenetics - Ding, Xiang; Yu, Xujiang; Chen, Jing; Su, Runlang; Li, Jinyou (Frontiers in Genetics, 2026)
The mitochondrial genome provides crucial information for understanding the evolution and phylogeny of various Apis cerana populations. Apis cerana-Southern China is a unique ecological type of Asian bee, A. cerana, primarily found in the coastal mountains of South China. Here, we used PacBio-HiFi sequencing to obtain the complete mitochondrial genome of A. cerana-Southern China and infer the phylogenetic relationships between A. cerana-Southern China and other A. cerana ecotypes. The mitochondrial genome of A. cerana-Southern China contains 16,137 bp and includes 13 protein-coding genes (PCGs), 22 tRNA genes, 2 rRNA genes, and an AT-rich region. The overall base composition is as follows: A (42.41%), C (9.59%), G (6.18%), and T (41.82%). The combined percentage of A and T (84.23%) is significantly higher than that of G and C. Among the 37 genes, 23 were located on the majority strand, while the remaining 14 were located on the minority strand. The phylogenetic tree based on the 13 PCGs showed that the genetic distance between A. cerana-Southern China, A. cerana-Central China, and A. cerana-Aba was closer. The complete mitochondrial genome sequence reported here would be useful for further phylogenetic analysis and conservation genetic studies in A. cerana-Southern China.